Pengaruh Pendidikan Dan Pelatihan Terhadap Etos Kerja Karyawan Pada PT PLN (Persero) ULP Grogol Kabupaten Kediri - Wahyunda Widiyanti; Aprillian Dian; Diana Ambarwati (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to find out: the influence of education on work ethic, the effect of training on work ethic, the influence of education and training on work ethic.This type of research uses a quantitative approach. The sample of this study was all employees at PT PLN (Persero) ULP Grogol, Kediri Regency as many as 35 employees. The sampling technique uses Saturated sampling. Data collection techniques usequestionnaires that have been tested for validity and reliability. The data analysis technique used is a classical assumption, multiple linear regression.The results of the study at the significance level of showed that: there was a positive and significant influence of education on work ethic, There is a positive and significant influence of training on work ethic, There is a simultaneous influence of education and training on work ethic.